2020
DOI: 10.6007/ijarped/v9-i2/7494
|View full text |Cite
|
Sign up to set email alerts
|

The Design of GIFTED Motivation Module Using the ADDIE Model Approaches Among the Gifted and Talented Students

Abstract: This study aims explore the process of development of GIFTED motivational module using the Design and Development Research (DDR) approach using the ADDIE Model. The development of the GIFTED motivational module for social issues involves the issues of perfectionism, social anxiety and overexcitabilities. Based on the analysis report on the need for perfectionism issues, social anxiety and overexcitabilities are three most common issues experienced by talented students. It is important to address the socio-emot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The implementation of ADDIE instructional design model as a framework indicated that the model was effective in designing and developing instructional learning module as it was conducted for specific populations for example gifted students (Abd Razak, Surat & Abd Majid, 2020), moral education students Zulkifli et al (2018) and nurses (Hsu et al, 2014). The development of the module was tested and found to be effective for Malaysian users specifically volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of ADDIE instructional design model as a framework indicated that the model was effective in designing and developing instructional learning module as it was conducted for specific populations for example gifted students (Abd Razak, Surat & Abd Majid, 2020), moral education students Zulkifli et al (2018) and nurses (Hsu et al, 2014). The development of the module was tested and found to be effective for Malaysian users specifically volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The ADDIE model of educational design is a established educational model that gives an organized technique for developing instructional materials (Shelton & Saltsman, 2006). The ADDIE development model includes 5 pastime sequel steps there are analysis, design, development, implementation, and evaluation (Abd Razak et al, 2020;Najuah et al, 2021). This ADDIE model is one of the strategies which can manual the development of structured modules.…”
Section: Methodsmentioning
confidence: 99%
“…According to (Seawright, 2003), among the issues taken into account during the implementation phase is the issue of implementation costs in the use of selected media, infrastructure issues in terms of hardware limitations, software limitations, bandwidth limitations, and internet access. Besides that, the implementation phase also concerned the module's duration,hich primarily depends on school hours (Abd Razak et al, 2020).…”
Section: Implementation Phasementioning
confidence: 99%